In situ cross-linked nonaqueous polymer electrolyte for zinc-metal polymer batteries and hybrid supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Kurian, Maria; Torris, Arun; Dilwale, Swati; Badiger, V. Manohar; Winter, Martin; Nair, Jijeesh Ravi; Kurungot, Sreekumar (Small, 2020)
This work reports the facile synthesis of nonaqueous zinc-ion conducting polymer electrolyte (ZIP) membranes using an ultraviolet (UV)-light-induced photopolymerization technique, with room temperature (RT) ionic conductivity values in the order of 10(-3)S cm(-1). The ZIP membranes demonstrate excellent physicochemical and electrochemical properties, including an electrochemical stability window of >2.4 V versus Zn|Zn(2+)and dendrite-free plating/stripping processes in symmetric Zn||Zn cells. Besides, a UV-polymerization-assisted in situ process is developed to produce ZIP (abbreviated i-ZIP), which is adopted for the first time to fabricate a nonaqueous zinc-metal polymer battery (ZMPB; VOPO4|i-ZIP|Zn) and zinc-metal hybrid polymer supercapacitor (ZMPS; activated carbon|i-ZIP|Zn) cells. The VOPO(4)cathode employed in ZMPB possesses a layered morphology, exhibiting a high average operating voltage of approximate to 1.2 V. As compared to the conventional polymer cell assembling approach using the ex situ process, the in situ process is simple and it enhances the overall electrochemical performance, which enables the widespread intrusion of ZMPBs and ZMPSs into the application domain. Indeed, considering the promising aspects of the proposed ZIP and its easy processability, this work opens up a new direction for the emergence of the zinc-based energy storage technologies.
Keywords: nonaqueous electrolytes; polymer electrolytes; postlithium batteries; Supercapacitors; zinc-metal batteries

Scalable synthesis of manganese-doped hydrated vanadium oxide as a cathode material for aqueous zinc-metal battery - Ghosh, Meena; Dilwale, Swati; Vijayakumar, Vidyanand; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2020)
Rechargeable aqueous zinc-metal batteries (ZMBs) are considered as potential energy storage devices for stationary applications. Despite the significant developments in recent years, the performance of ZMBs is still limited due to the lack of advanced cathode materials delivering high capacity and long cycle life. In this work, we report a low-temperature and scalable synthesis method following a surfactant-assisted route for preparing manganese-doped hydrated vanadium oxide (MnHVO-30) and its application as the cathode material for ZMB. The as-prepared material possesses a porous architecture and expanded interlayer spacing. Therefore, the MnHVO-30 cathode offers fast and reversible insertion of Zn2+ ions during the charge/discharge process and delivers 341 mAh g(-1) capacity at 0.1 A g(-1). Moreover, the MnHVO-30 parallel to Zn cell retains 82% of its initial capacity over 1200 stability cycles, which is higher compared to that of the undoped system. Besides, a quasi-solid-state home-made pouch cell with an area of 3.3 x 1.6 cm(2) and 3.6 mg cm(-2) loading is assembled, achieving 115 mAh g(-1) capacity over 100 stability cycles. Therefore, this work provides an easy and attractive way for preparing efficient cathode materials for aqueous ZMBs.
Keywords: anionic surfactant; hydrated vanadium pentoxide; Nafion ionomer membrane; post-lithium battery; quasi-solid-state battery

Naphthalene dianhydride organic anode for a `rocking-chair' zinc-proton hybrid ion battery - Ghosh, Meena; Vijayakumar, Vidyanand; Kurian, Maria; Dilwale, Swati; Kurungot, Sreekumar (Dalton Transactions, 2021)
Rechargeable batteries consisting of a Zn metal anode and a suitable cathode coupled with a Zn2+ ion-conducting electrolyte are recently emerging as promising energy storage devices for stationary applications. However, the formation of high surface area Zn (HSAZ) architectures on the metallic Zn anode deteriorates their performance upon prolonged cycling. In this work, we demonstrate the application of 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTCDA), an organic compound, as a replacement for the Zn-metal anode enabling the design of a `rocking-chair' zinc-proton hybrid ion battery. The NTCDA electrode material displays a multi-plateau redox behaviour, delivering a specific discharge capacity of 143 mA h g(-1) in the potential window of 1.4 V to 0.3 V vs. Zn|Zn2+. The detailed electrochemical characterization of NTCDA in various electrolytes (an aqueous solution of 1 M ZnOTF, an aqueous solution of 0.01 M H2SO4, and an organic electrolyte of 0.5 M ZnOTF/acetonitrile) reveals that the redox processes leading to charge storage involve a contribution from both H+ and Zn2+. The performance of NTCDA as an anode is further demonstrated by pairing it with a MnO2 cathode, and the resulting MnO2||NTCDA full-cell (zinc-proton hybrid ion battery) delivers a specific discharge capacity of 41 mA h g(total)(-1) (normalized with the total mass-loading of both anode and cathode active materials) with an average operating voltage of 0.80 V.

Electrodeposited layered sodium vanadyl phosphate (NaxVOPO4 center dot nH(2)O) as cathode material for aqueous rechargeable zinc metal batteries - Dilwale, Swati; Ghosh, Meena; Vijayakumar, Vidyanand; Kurungot, Sreekumar (Energy & Fuels, 2022)
Aqueous rechargeable zinc metal batteries (ARZMBs) present a safer and cost-effective solution for energy storage in stationary applications. However, a major challenge is the lack of suitable cathode materials simultaneously exhibiting high operating voltage and long cycling stability. Herein, we report the polyanionic sodium-intercalated layered vanadyl phosphate [NaxVOPO4 center dot nH(2)O (NVP)] as a suitable high-voltage and stable cathode for ARZMBs. This work employs a simpler electrochemical route (electrodeposition) for the synthesis of NVP over functionalized carbon fiber substrates and its application as a binder-free cathode in ARZMBs. The electrodeposited NVP possesses a morphology of vertically aligned well-separated nanosheet bundles resembling a flower. When used as the ARZMB cathode, the NVP electrode delivers a specific discharge capacity of 100 mA h g(-1) at 0.033 A g(-1) and high cycling stability (98% retention of the initial capacity over 1100 cycles at 0.333 A g(-1)) in a mild aqueous electrolyte with moderate zinc salt concentration. The observed electrochemical performance of NVP is credited to the synergistic effect of unique nanoflower morphology, the pillaring effect offered by the intercalated Na, and the intimate contact of the active material with the carbon fiber network. These factors are favorable for enhancing the transport of the electrolyte ions and electrons and maintaining the structural stability of the electrode during long-term cycling. The NVP electrode could also deliver appreciable performance (a discharge capacity of 73 mA h g(-) 1 and a current density of 0.033 A g(-1)) in quasi-solidstate ARZMB cells employing PVA/Zn(CF3SO3)(2) gel electrolyte.

Binder-free and flexible VOPO4/CNT film as cathode for aqueous rechargeable Zn-metal battery - Dilwale, Swati; Babu, Athira; Puthiyaveetil, Priyanka Pandinhare; Kurian, Maria; Ghosh, Meena; Kurungot, Sreekumar (Advanced Sustainable Systems, 2023)
Aqueous rechargeable Zn-metal batteries (AZMBs) are promising energy storage aids due to their inherent safety, low cost, and competent performance, with prospects in stationary and portable applications. In this regard, one of the critical requirements is developing electrodes that can adapt to mechanical deformation without compromising the charge storage performance. The current work demonstrates the development of a binder-free and mechanically flexible composite cathode film (VP/fCNT-F, where `F' stands for the film) based on VOPO4 (VP) and functionalized carbon nanotubes (fCNTs). The VP/fCNT-F film processing involves simple vacuum filtration of the composite obtained from the in-situ reaction of the fCNTs and the VP precursor in an aqueous medium. The functionalization of carbon nanotube (CNT) is important for the homogenous dispersion of VP and fCNT. The VP/fCNT-F electrode is used as a monolithic electrode in AZMB cells in combination with both liquid and quasi-solid-state gel polymer electrolytes. Besides, the utility of the VP/fCNT-F electrode in a flexible battery configuration is also demonstrated. Interestingly, in both the coin-cell and flexible configurations, the VP/fCNT-F electrode delivers a comparable discharge capacity of 90 and 78 mAh g(-1), respectively (at 0.1 A g(-1)), validating the advantage of the binder-free VP/fCNT-F electrode for AZMBs.
Keywords: binder-free cathodes; flexible batteries; layered VOPO4; polymer gel electrolytes; self-standing flexible films

Cathode|electrolyte interface engineering by a hydrogel polymer electrolyte for a 3D porous high-voltage cathode material in a quasi-solid-state zinc metal battery by in situ polymerization - Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Dilwale, Swati; Kanheerampockil, Fayis; Kurungot, Sreekumar (SMALL, 2024)
This work highlights the development of a superior cathode|electrolyte interface for the quasi solid-state rechargeable zinc metal battery (QSS-RZMB) by a novel hydrogel polymer electrolyte using an ultraviolet (UV) light-assisted in situ polymerization strategy. By integrating the cathode with a thin layer of the hydrogel polymer electrolyte, this technique produces an integrated interface that ensures quick Zn2+ ion conduction. The coexistence of nanowires for direct electron routes and the enhanced electrolyte ion infiltration and diffusion by the 3D porous flower structure with a wide open surface of the Zn-MnO electrode complements the interface formation during the in situ polymerization process. The QSS-RZMB configured with an integrated cathode (i-Zn-MnO) and the hydrogel polymer electrolyte (PHPZ-30) as the separator yields a comparable specific energy density of 214.14 Wh kg(-1) with that of its liquid counterpart (240.38 Wh kg(-1), 0.5 M Zn(CF3SO3)(2) aqueous electrolyte). Other noteworthy features of the presented QSS-RZMB system include its superior cycle life of over 1000 charge-discharge cycles and 85% capacity retention with 99% coulombic efficiency at the current density of 1.0 A g(-1), compared to only 60% capacity retention over 500 charge-discharge cycles displayed by the liquid-state system under the same operating conditions.
Keywords: cathode-electrolyte interface tuning; dendrite inhibition; epitaxial zinc deposition; hydrogel polymer electrolyte; In situ polymerization; Quasi solidstate rechargeable zinc metal battery

High-voltage symmetric supercapacitor electrodes via in situ synthesized multiwalled carbon nanotube-doped perylenebisimide-based donor-acceptor conjugate polymer P(PDI2OD-T2) - Wavhal, Aryan Anurath; Dilwale, Swati; Puthiyaveetil, Priyanka Pandinhare; Kakde, Navnath R.; Prakash, Medha; Kurungot, Sreekumar; Asha, S. K. (Journal of Physical Chemistry C, 2024)
This study presents the design and synthesis of a donor-acceptor pi-conjugated polymer composite P(PDI2OD-T2)/MWCNT tailored for high-voltage symmetric supercapacitor applications. The synthesis of P(PDI2OD-T2)/MWCNT was expedited by adopting a novel in situ polymerization technique that modifies the traditional Stille polymerization process. Incorporating approximately 33% by weight of multiwalled carbon nanotubes (MWCNT) into the polymer matrix, referred to as P-2, significantly enhances its conductivity, surface area, and porosity. These improvements in the material properties contribute to the superior electrochemical performance of the composites by promoting efficient electrolyte ion transport across the electrode-electrolyte interfaces. The symmetric supercapacitor devices fabricated with P-2 electrodes employing both liquid organic (LE-P-2||P-2) and quasi-solid-state gel (QSS- P-2||P-2) electrolytes demonstrate capacitance values of 85.4 and 84.2 F g(-1), respectively, at a current density of 0.25 A g(-1), while operating at a high-voltage window of 3.1 V. Moreover, these devices exhibit robust cycling stability, maintaining approximately 70% of their initial capacitance over 45,000 cycles with a coulombic efficiency of 96%. The successful demonstration of a quasi-solid-state symmetric supercapacitor underscores the potential of flexible energy storage solutions, as evidenced by a PMMA LiClO4 gel electrolyte prototype. This flexible device not only maintains structural integrity but also achieves an impressive power density of 18,600 W kg(-1) and an energy density of 112.4 Wh kg(-1), indicating its practical viability for real-world applications.

Insights on prussian blue analogue cathode material engineered with polypyrrole surface protection layer for aqueous rechargeable zinc metal battery - Puthiyaveetil, Priyanka Pandinhare; Nair, Aathira; Dilwale, Swati; Kurian, Maria; Joshi, Kavita; Kurungot, Sreekumar (Small, 2024)
One of the key intricacies against using Prussian blue analogues (PBAs) in aqueous batteries is their gradual dissolution in aqueous electrolytes, resulting in inadequate cycling stability. Besides, the rate capability of PBAs is limited due to their poor electrical conductivity. To overcome these challenges, it is essential to tune the physical and chemical properties of PBAs at the nano regime without affecting the inherent charge storage properties, especially at high-voltage operating conditions. Through this work, a strategy is demonstrated to enhance the electrochemical performance of vanadium-based PBA (V-PBA) by surface engineering using a conducting polymer nano-skin (V-PBA/PPy) for aqueous zinc metal batteries. The polypyrrole (PPy) nano-skin over the V-PBA nanoparticles acts as an electron percolation path to ameliorate the poor electronic conductivity of the otherwise pristine V-PBA. Interestingly, the V-PBA with an optimized polypyrrole coating (V-PBA/PPy-2) exhibits an enhanced specific capacity (173 mAh g-1 at 0.10 A g-1) than the pristine V-PBA counterpart (80 mAh g-1) and 85% capacity retention up to 500 cycles. The DFT calculation confirms the synergistic interaction between PPy and V-PBA and the presence of PPy favors the adsorption of Zn.
Keywords: aqueous rechargeable zinc metal battery; DFT; polypyrrole coating; Prussian blue analogue; surface protection layer

Interlayer space engineering-induced pseudocapacitive zinc-ion storage in holey graphene oxide-bearing vertically oriented MoS2 nano-wall array cathode for aqueous rechargeable Zn metal batteries - Babu, Athira; Dilwale, Swati; Kurungot, Sreekumar (Small, 2024)
Transition metal dichalcogenides, particularly MoS2, are acknowledged as a promising cathode material for aqueous rechargeable zinc metal batteries (ARZMBs). Nevertheless, its lack of hydrophilicity, poor electrical conductivity, significant restacking, and restricted interlayer spacing translate into inadequate capacity and rate performance. Herein, the unique porous structure and additional functional groups present in holey graphene oxide (hGO) are taken advantage of to dictate the vertical growth pattern of oxygen-doped MoS2 nanowalls (O-MoS2/NW) over the hGO surface. Compared to conventional graphene oxide (GO), the presence of nano-pores in hGO facilitates the homogeneous dispersion of Mo precursors and provides stronger interaction sites, promoting the uniform vertical alignment of O-MoS2/NW. The synergistic interaction between O-MoS2-NW and hGO translates to enhanced electron conductivity, efficient electrolyte penetration, enhanced interlayer spacing, reduced restacking, and enhanced surface area. As a consequence of precise control of various factors that decide the overall battery performance, a high discharge capacity (227 mAh g(-1) at 100 mA g(-1)) cathode material with significantly lower charge transfer resistance (66 Omega) compared to pristine O-MoS2 (153 Omega) is developed. These findings underscore the potential of hGO as a multifunctional platform for nanoengineering high-performance cathode materials for the next generation of efficient and durable ARZMBs.
Keywords: aqueous rechargeable zinc metal battery; holey graphene oxide; hydrophilicity tuning; interlayer space engineering; oxygen-doped MoS2; transition metal dichalcogenide; vertical nanowall

Phytic acid customized hydrogel polymer electrolyte and prussian blue analogue cathode material for rechargeable zinc metal hydrogel batteries - Dilwale, Swati; Puthiyaveetil, Priyanka Pandinhare; Babu, Athira; Kurungot, Sreekumar (Small, 2024)
Zinc anode deterioration in aqueous electrolytes, and Zn dendrite growth is a major concern in the operation of aqueous rechargeable Zn metal batteries (AZMBs). To tackle this, the replacement of aqueous electrolytes with a zinc hydrogel polymer electrolyte (ZHPE) is presented in this study. This method involves structural modifications of the ZHPE by phytic acid through an ultraviolet (UV) light-induced photopolymerization process. The high membrane flexibility, high ionic conductivity (0.085 S cm-1), improved zinc corrosion overpotential, and enhanced electrochemical stability value of approximate to 2.3 V versus Zn|Zn2+ show the great potential of ZHPE as an ideal gel electrolyte for rechargeable zinc metal hydrogel batteries (ZMHBs). This is the first time that the dominating effect of chelation of phytic acid with M2+ center over H-bonding with water is described to tune the gel electrolyte properties for battery applications. The ZHPE shows ultra-high stability over 360 h with a capacity of 0.50 mAh cm-2 with dendrite-free plating/stripping in Zn||Zn symmetric cell. The fabrication of the ZMHB with a high-voltage zinc hexacyanoferrate (ZHF) cathode shows a high-average voltage of approximate to 1.6 V and a comparable capacity output of 63 mAh g-1 at 0.10 A g-1 of the current rate validating the potential application of ZHPE. A novel phytic acid (PA) modulated zinc hydrogel polymer electrolyte (ZHPE) as an efficient electrolyte and separator for rechargeable Zn-metal hydrogel batteries (ZMHB) is designed. The zincophilic, and hydrogen bonding characteristics of ZHPE help in regulating uniform dendrite-free Zn-deposition over the Zn anode surface. ZHPE in combination with the developed high-voltage zinc hexacyanoferrate (ZHF) cathode performs as an efficient ZMHB. image
Keywords: high voltage cathode; high-conducting gel polymer electrolyte; phytic acid; rechargeable Zn-metal hydrogel batteries; Zn hydrogel polymer electrolyte

Anode|electrolyte|cathode interface engineering to develop a robust zinc metal hydrogel battery - Dilwale, Swati; Babu, Athira; Kanheerampockil, Fayis; Torris, Arun; Puthiyaveetil, Priyanka Pandinhare; Bhat, Suresh; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2025)
The poor electrode-electrolyte interfaces in quasi-solid-state zinc metal batteries often hinder Zn2+ ion transport due to the poor compatibility of the gel electrolyte with the electrodes. This report proposes a dual-interface engineering strategy across the anode, cathode, and separator using a single hydrogel polymer electrolyte (HPE). The integration of vanadyl phosphate functionalized carbon nanotubes (VP/fCNT) into a commercial glass fiber (GF) separator, followed by a thin hydrogel coating and UV-light photopolymerization, resulted in a dual-interface engineered cathode-separator-electrolyte structure (VP/IC-EGF). To mitigate the dendritic growth, an artificial solid electrolyte interface was developed on Zn foil (AEI@Zn). The engineered GF (EGF) demonstrates a room-temperature conductivity of 6.5 mS cm-1 and a high electrochemical stability window of 2.4 V vs. Zn|Zn2+. The symmetric cell with AEI@Zn|EGF|AEI@Zn exhibits exceptional plating/stripping stability over 1400 h at a current density of 0.1 mA cm-2 and a capacity of 0.1 mAh cm-2. Moreover, the low-volume cell (AEI@Zn & Vert;VP/IC-EGF), featuring the dual-interface-engineered cathode-separator-electrolyte, demonstrates outstanding cycling stability with over 3000 charge-discharge cycles at a current rate of 1.0 A g-1, retaining 98-99% of its initial capacity and showing high coulombic efficiency. These findings underscore the significant impact of interface engineering on enhancing the performance of ZMBs.